The Utilisation of Botanical Pesticide as Pest Control in The Management of Organic Vegetable Farming - Faradila Amir; Sri Wiyatiningsih (Nusantara Science and Technology Proceedings, 2022)
Botanical pesticides are eco-friendly pesticides derived from plant extracts. Botanical pesticides can be used as pest control in organic vegetable farming. Some pests are known to attack organic vegetables, such as the large cabbage-heart caterpillar (Crocidolomia pavonana) and aphids (Myzus persicae) attack the cauliflower plant; grasshopper (Atractomorpha similis) and flea beetle (Phyllotreta nigripes) attack the green mustard plant, and the beetle (Epilachna borealis) attacks tomato plants. Some botanical pesticides used to control these pests are derived from soursop leaf extract, paitan leaf extract, and neem fruit extract. The results of the application of these pesticides can reduce the pest population; the percentage of pest population decline in C. pavonana is 30%; M. persicae s by 65.5%; A. similis by 66.6%; Ph. nigripes by 60%; and E. borealis as much as 66.6%.